Efficient Object Detection and Voice-Assisted Navigation for the Visually Impaired: The Smart Hat Approach - Memoona Sami; Dua Agha; Junaid Baloch; Amirita Dewani; Kohal Deep Maheshwari (Sukkur IBA Journal of Computing and Mathematical Sciences)
People with visual impairments encounter many obstacles and challenges while navigating daily surroundings which typically affect their mobility, independence, and overall quality of life. In response to these challenges, this paper presents the development of the "Smart Hat," a wearable gadget that helps visually impaired people by offering real-time object detection and voice assistance. The module utilized in Smart Hat is ESP32-CAM used to record live video transmitted wirelessly to a mobile application. The TensorFlow framework is utilized by the device to provide precise and effective object recognition which is then transmitted through voice assistance via headphones. This solution provides an intuitive user interface along with auditory cues to help the blind person navigate their surroundings safely. With an accuracy rate of more than 91%, Smart Hat offers a lightweight, portable, and affordable substitute for traditional assistive technologies like guide dogs or costly electronic aids. The goal of Smart Hat technology is to empower individuals with visual impairment by giving them more independence and self-assurance in their surroundings.